The Influence of Hermann Günther Grassmann and Robert Grassmann on Ernst Schröder’s Algebra of Logic - Peckhaus, Volker (Hermann Günther Graßmann (1809–1877): Visionary Mathematician, Scientist and Neo-humanist Scholar. Papers from a Sesquicentennial Conference)
Rezensionen: Modern Logic 7 (1997), 88 (I.H. Anellis, “Bibliographic Notic-es”); MR 97j:01024 (J.W. Dauben); Zbl. Math. 907.01026 (J.J. Cross).